2022
DOI: 10.1111/nph.18621
|View full text |Cite
|
Sign up to set email alerts
|

Inositol polyphosphates‐regulated polyubiquitination of PHR1 by NLA E3 ligase during phosphate starvation response in Arabidopsis

Abstract: Summary Phosphate (Pi) availability is a major factor limiting plant growth and development. The key transcription factor controlling Pi‐starvation response (PSR) is PHOSPHATE STARVATION RESPONSE 1 (PHR1) whose transcript levels do not change with changes in Pi levels. However, how PHR1 stability is regulated at the post‐translational level is relatively unexplored in Arabidopsis thaliana. Inositol polyphosphates (InsPn) are important signal molecules that promote the association of stand‐alone SPX domain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, studies on the post‐translational regulation of PHR1 are still lacking. To date, only one SUMO‐E3 ligase, SIZ1, has been shown to mediate PHR1 activity in response to Pi starvation (Miura et al, 2005), and the E3 ligase NLA has been shown to mediate PHR1 stability in Arabidopsis (Park et al, 2023). The SINA E3 ligases are member of the RING E3 ligase family, which is widely involved in regulating plant growth and development and stress responses (Xie et al, 2002; Ning et al, 2011; Bao et al, 2014; Miao et al, 2016; Fan et al, 2017; Yang et al, 2017; Zhang et al, 2019; Lee et al, 2021; Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on the post‐translational regulation of PHR1 are still lacking. To date, only one SUMO‐E3 ligase, SIZ1, has been shown to mediate PHR1 activity in response to Pi starvation (Miura et al, 2005), and the E3 ligase NLA has been shown to mediate PHR1 stability in Arabidopsis (Park et al, 2023). The SINA E3 ligases are member of the RING E3 ligase family, which is widely involved in regulating plant growth and development and stress responses (Xie et al, 2002; Ning et al, 2011; Bao et al, 2014; Miao et al, 2016; Fan et al, 2017; Yang et al, 2017; Zhang et al, 2019; Lee et al, 2021; Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pi starvation causes a non-significant reduction in PHR1 expression, but the transcriptional activity of this gene is mediated by the small ubiquitin-related modifier (SUMO)-E3 ligase SAP AND MIZ1 DOMAIN-CONTAINING LIGASE1 (SIZ1) under Pi starvation conditions (Miura et al, 2005). A recent study showed that the E3 ligase NITROGEN LIMI-TATION ADAPTATION (NLA) E3 ligase mediates PHR1 degradation (Park et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the concentrations of callose, phytoalexin, SA and JA in the leaves of nla1 mutants are increased, indicating that NLA1 may be a negative regulator involved in plant immunity (Val-Torregrosa et al 2022). NLA1 may control the JA signaling pathway by regulating the protein level of PHR1 with a PP-InsPs-dependent manner (Park et al 2022; Fig. 3).…”
Section: Crosstalk Between P Status-and Ja-signalingmentioning
confidence: 99%
“…It was shown that the SPX domain of NLA1 not only interacts with the Pi transporter PHT1s, but also with the nitrate transporter NRT1;7 (Lin et al 2013;Liu et al 2017). Although it was revealed that NLA1 mediates the ubiquitination of PHR1 in a PP-InsPs-dependent manner (Park et al 2022), it remains largely unknown whether PP-InsPs affect the NLA1-PHT1s module to control Pi uptake, or on the NLA1-NRT1;7 module to regulate nitrate status in plants. The SPX domain of NLA2 also contains a conserved PP-InsPs binding site, suggesting that NLA2 may also work coordinately with PP-InsPs to control P status in plants (Secco et al 2012;Jung et al 2018).…”
Section: Spx-ring Protein Subfamilymentioning
confidence: 99%